Catalytic Role of Lewis Acids in ArIO‐Mediated Oxidative Fluorination Reactions Revealed by DFT Calculations. Issue 15 (9th April 2020) - Farshadfar, Kaveh; Abdolalian, Payam; Ariafard, Alireza
Abstract : Density functional theory (DFT) at the SMD/M06‐2X/def2‐TZVP//SMD/M06‐2X/SDD, 6‐31G(d) level was performed to interrogate the mechanistic details of two oxidative fluorination reactions mediated by hypervalent iodosoarenes (ArIO) in the presence of Lewis acid BF3 : (i) formation of a 3‐fluoropyrrolidine from a homoallylic amine and (ii) formation of a fluorinated oxazoline from a benzamide. We found that in both cases, ArIO needs two Lewis acids to be sufficiently activated to mediate the oxidative reactions. When two Lewis acids bind to ArIO, its LUMO mainly centred on the iodine(III) atom becomes energetically more available, resulting in it interacting more strongly with the C–C π orbital of the organic substrate and thus the rate‐determining step of the reaction (an intramolecular nucleophilic attack) being accelerated. Finally, one of these Lewis acids serves as the catalyst and the other one supplies a fluorine atom to the organic substrate. A clear understanding of how ArIO reagents are activated in oxidation of organic substrates could be helpful in designing new oxidative reactions mediated by such hypervalent iodine compounds. Abstract : ArIO· BF3 was believed to be the active species for the organic transformations mediated by iodosoarene (ArIO) in the presence of BF3 Lewis acid. This study for the first time indicates that this is not a true statement and the transformations are mediated by ArIO· BF3 if a Lewis acid is involved as the catalyst in the process.